Salvage autologous fascial sling after failed anti-incontinence surgeries: Long term follow up - Sharifiaghdas, Farzaneh; Mahmoudnejad, Nastaran; Honarkar Ramezani, Mehdi; Shemshaki, Hamidreza; Ameri, Fatemeh (Urology Journal, 2019)
OBJECTIVE: To evaluate long term outcomes of autologous pubovaginal fascial sling (AFPVS) as a salvage procedure following different types of failed anti-incontinence surgeries. MATERIALS AND METHODS: We retrospectively reviewed medical records of patients who had undergone salvage AFPVS after any kind of anti-incontinence surgery from 2005-2015 at our medical center. Patients were contacted by telephone. Revised Urinary Incontinence Scale (RUIS) was used to determine the success rate. RESULTS: A total of 40 patients out of 51 were successfully contacted. Mean patient age was 50.8± 9.8 years (range30-75) and mean follow up was 62.6±32.4 months (range12-120). Of 40 patients, 14(35%) had pure SUI and 26(65%) complained of mixed urinary incontinence. A total of 15(37.5%) patients had a failed Burch colposuspention, 5(12.5%) TVT, 8(20%) TOT, 3 (7.5%) AFPVS and five (12.5%) patients had history of failed mini-sling procedure. Four (10%) patients had undergone more than one anti incontinence surgeries. Overall success rate was 65% in our study. New onset urge urinary incontinence was detected in 25% of patient which was negatively associated with satisfaction and recommendation. There was no statistically significant correlation between mixed urinary incontinence, type or number of previous failed surgeries with success however presence of pure SUI had a strong COCLUSION: Autologous pubovaginal fascial sling might be considered as a safe and efficacious salvage surgical option following failed midurethral slings, Burch colposuspention and even AFPVS itself. It will provide reasonable long term results with no major complications.